MOSLEM WOMEN’S RESISTANCE AGAINST SECULARIST’S DOMINATION IN ORHAN PAMUK’S SNOW NOVEL - Siti Kholisah; Miftahul Huda; Lusi Setyorini (Edulitics (Education, Literature, and Linguistics) Journal, 2017)
Headscarves controversy still overshadows the life of modern Turkey. In Orhan Pamuk‟s Snow, to modernize the state, the secularist elites implement secularism by unveiling women. Implementation is through banning the headscarves wearing in public buildings, including school, that its executions dominate Moslem women. In reverse, Moslem women, who are represented by the characters named Kadife, Hande, and Teslime, resist the domination to defend their rights upon wearing the headscarves for the sake of practicing their religion, Islam. Grounded upon the findings, this study questions upon (1) how is secularist‟s domination upon Moslem women depicted in Orhan Pamuk‟s Snow? and (2) how do Moslem women show their resistance against secularist‟s domination in Orhan Pamuk‟s Snow? The researcher used qualitative research, especially mimetic approach with descriptive analysis method is applied in this study. Data collecting used mimetic approach research, researcher used four step to analyze (1) Classifying the data dealt with the object of the study, (2) Interpreting and making correlation between the data and thestatement of problems, (3) Answering the questions stated in the statement of problems by considering the result of the data analysis,(4) Drawing the conclusion based on the result of the data analysis. The result of this study shows that the secularist‟s domination manifests itself into five forms: domination through policy-making, threat, onstage play, derogation, and hegemony. Meanwhile, Moslem women‟s resistance manifests itself into two major forms: outward resistance (public transcript), which is practiced through demonstration and insult, and inward resistance (hidden transcript), which is practiced through suicide and vis-à-vis dialogue. The researcher suggested to the reader to make knowledge and lesson from this study especially about secularist domination in modern turkey.